2000
DOI: 10.1590/s0036-46652000000400001
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection in children with Down syndrome in a day-care center in Brazil

Abstract: SUMMARYThis study evaluates the transmission of CMV infection in 120 children aged 1 to 15 years with Down syndrome who attended a day-care center for handicapped children in São Paulo, Brazil. A blood sample was obtained from each children at the beginning of the study for detection of IgG and IgM cytomegalovirus (CMV) antibodies by an immunofluorescence assay. Samples of saliva and urine were obtained every 3 months from the children with CMV antibodies to detect shedding of the virus by culture in human for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
(23 reference statements)
1
14
0
1
Order By: Relevance
“…Some of the results are in line with the ones of other authors [26,27,17,18] and they may reflect an adaptive mechanism in adults with Down syndrome in order to sustain an efficient response…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some of the results are in line with the ones of other authors [26,27,17,18] and they may reflect an adaptive mechanism in adults with Down syndrome in order to sustain an efficient response…”
Section: Discussionsupporting
confidence: 91%
“…The response against vaccinal antigens and other antigens such as pertussis, rubella, measles, hepatitis A and B was better in DS patients when compared with other groups [10-14]. However other studies disagree with this affirmation [15-18]. …”
Section: Introductionmentioning
confidence: 98%
“…However, recent evidence has demonstrated that mucosal shedding of HCMV occurs commonly in many healthy individuals (do Canto et al, 2000;Lucht et al, 1998;Shen et al, 1996) and very frequently in immunocompromised patients (Diamond et al, 2000;Fidouh-Houhou et al, 2001;Lucht et al, 1998;Mostad et al, 2000). In this study, RhCMV shedding was detected consistently in many animals, indicating low-level, persistent infection.…”
Section: The Pattern Of Rhcmv Detection Is Very Similar To What Is Knmentioning
confidence: 43%
“…Only two of these studies looked at seroconversion in children, finding seroconversion rates of 26% in children with Down syndrome in day care [19] and 4.3% in children enrolled from paediatric well child clinics where day-care attendance was found to be a risk factor for seroconversion [20].…”
Section: Results In Day-care Settings: Children Parents and Providersmentioning
confidence: 99%